The role of e-books in language learning: A bibliometric analysis - Sari Rakhamwati; Setiawan Edi wibowo; Aditya Dwi Hanggara; Shakila Che Dahalan; Hafizhah Rahmiati Auliya; Ika Susianti (Jurnal Prima Edukasia, 2026)
Abstract: Technological advancements have facilitated access to electronic books (e-books), which are becoming increasingly popular as language learning media due to their interactive multimedia features. This bibliometric study aims to map the development of research on e-books in language learning using data from Scopus analyzed with the Bibliometrix package. The analysis reveals that the literature is centered around themes of reading literacy and the integration of educational technology, highlighting e-books as a key component in supporting reading comprehension and enhancing motivation in language learning. The study also finds that research is predominantly contributed by developed countries (notably China, the United States, and Japan), supported by strong institutional funding, while international collaboration remains limited. The contribution of this study is to provide a comprehensive map of research trends, collaboration networks, and dominant themes in the field of e-books for language learning, while also identifying research gaps that warrant further investigation. The comprehensive bibliometric analysis maps publication trends, author collaboration, and key topics related to e-books in language learning. The findings indicate that students’ reading literacy and the use of educational technology are dominant themes, with e-books playing a vital role in improving reading comprehension and learning engagement. Cross-country research collaboration remains limited, highlighting the need to strengthen global scientific networks to bridge research capacity gaps in this field.. Keywords: bibliometric analysis, electronic books (e-books), digital literacy, language learning